ANALISIS KARAKTER UTAMA DALAM NOVEL IF I STAY KARYA GYLE FORMAN - PARUNTU, KEZIA ELISABETH NOVITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research, entitled â€œAnalisis Karakter Utama dalam Novel If I Stay Karya Gyle Formanâ€, is intended to give explanation about the main character namely Mia Hall as portrayed in the novel. The objectives of this research are to identify and analyze Mia Hallâ€™s character, using Stantonâ€™s theory. Stanton suggests the four specific ways on how to analyze a character: they are what the character says and thinks, what the character does, interactions among characters, and action. The methodology used consists of three phases namely; preparation, data collection, and data analysis. The data were taken from Gyle Formanâ€™s novel and analyzed using intrinsic approach to describe Mia Hallâ€™s character. The research findings show that Mia Hallâ€™s character is portrayed in the novel as being frustrated, panic, sad, hopeless, helpless, but at the same time she is full of love. All this is depicted through her expressions, action and dialogue, as well as their interaction among characters in the novel. Â  Keywords: Analysis main character,Gyle Forman, Mia Hall, Stanton.